2020
DOI: 10.29035/rcaf.21.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación y validación de los cuestionarios de apoyo a la autonomía y estilo controlador a la educación física: relación con el feedback

Abstract: Adaptación y validación de los cuestionarios de apoyo a la autonomía y estilo controlador a la educación física: relación con el feedback. Revista

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
0
17
0
6
Order By: Relevance
“…Responses are collected on a Likert scale ranging from 1 (definitely no) to 5 (definitely yes). Previous research has confirmed the reliability of this scale in the sport context (e.g., [ 46 ]) and in the physical education domain (e.g., [ 45 ]).…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Responses are collected on a Likert scale ranging from 1 (definitely no) to 5 (definitely yes). Previous research has confirmed the reliability of this scale in the sport context (e.g., [ 46 ]) and in the physical education domain (e.g., [ 45 ]).…”
Section: Methodsmentioning
confidence: 74%
“…Coaches’, father’s, mother’s, and teammates’ controlling style. To assess the swimmer’s perception of the controlling style of the coach, father, mother, and teammates, the Spanish version of the Controlling Style Scale was adapted to this study [ 45 ]. This unidimensional scale is composed of nine items (e.g., “Talks continuously and does not allow me to make contributions at training/at home”) starting with the statement “During training and/or at home, your coach, your father, your mother, your teammates...”.…”
Section: Methodsmentioning
confidence: 99%
“…The Autonomy Support Scale. The ASS-PE [23] was employed in this study and consists of eleven items, which assess athletes’ perceived autonomy support from their coaches. The stem for the items is, “In my sport, my coach(es)…” and a sample question is “Help(s) us to understand the purpose of the activities in which we are involved”.…”
Section: Methodsmentioning
confidence: 99%
“…The Controlling Style Scale. The CSS-PE [23] was used in the study and consists of nine items that assess athletes’ perceptions of a controlling coaching style. The stem for each item is, “In my sport, my coach…” and a sample item is, “Talks constantly and doesn’t allow us to provide input during practice”.…”
Section: Methodsmentioning
confidence: 99%
“…Por otro lado, cabe destacar que el estudio del clima interpersonal motivacional se aborda teniendo en cuenta las estrategias de apoyo a todas las necesidades psicológicas básicas y evitando centrarse únicamente en el apoyo a la autonomía, como se viene demandando en la actualidad (Fierro-Suero et al, 2020;Moreno-Murcia et al, 2020;Vasconcellos et al, 2020). De esta forma, además de ver el grado en el que el profesorado apoya o controla cada NPB, se puede calcular el coeficiente CIM, una medida global del clima interpersonal motivacional que puede ser útil en muchos casos (Fierro-Suero et al, 2020).…”
Section: Autonomíaunclassified